Cytopathological study of 100 cases of varicella and its value in the differential diagnosis of smallpox - Castro García, Jorge (1967)
Disclosed cytologic features of a cell type with diagnostic value in chickenpox , called Giant Cell Features , Multinucleated Giant Cells , Atypical cells or " pseudotumoral " . These cells acquire cyto logical morphologically distinguishable characteristics , dye , quantitative , and fine percentage , according to the stage of the rash variceloso are. In phase transparent vesicle are usually round or oval , with one or two giant nuclei , acidophilic staining affinity discreetly . In phase turbid or opalescent vesicle there is a tendency of irregular deformation of cells and nuclear multi-segmentation ( multinucleated ) and acquire more acidophilic staining in the previous phase. At the stage of pustule are often spherical with giant core and take an acidophilus frankly coloring with Leishman . The cytoplasm of these cells is scarce and generally takes basophilic staining in the three phases of variceloso rash. In all of them there is loss of core - cytoplasmic ratio . Almost all of these cells have a clear perinuclear halo, perfectly highlighted in the cell cytoplasm. In none of these cells has identified the nucleolus . The size of these cells is also variable ( 40 to 60 microns ) . The average standard size, average core - cell maximum size , the average core - cell minimum size are higher in the turbid vesicle phase or in phase opalescent transparent vesicle and pustule ; in this last considerably less than in the above. Quantitative assessment of the percentage of these cells relative to other also varies the phase of the varicella vesicle , being 100% in the clear vesicle , 40 to 60% in the opalescent vesicle and 2 % in the pustule . These cells have not been found in the three cases of smallpox have been studied from the point of view cytological , following the same procedure used in technical chickenpox. Pathological studies of representative complementary in chickenpox and in three cases of smallpox cases confirm the presence of these cells in the first and Guarnieri corpuscle in the second.